Biodegradation of low-density polyethylene by the bacterial strains isolated from the dumping site community - Khampratueng, Pornya; Rice, Daniel; Anal, Anil Kumar (Discover applied sciences, 2024)
Low-density polyethylene (LDPE) is the predominant single-use plastic and rarely decomposes after disposal. The primary objective of this study was to identify potential bacteria capable of degrading LDPE plastic and investigating the biochemical pathways of this process. Bacteria were isolated from soil samples collected from a local garbage dumping site in Thailand and tested on their capability to degrade LDPE plastic. Two of the bacteria isolated from the dumping site, Bacillus sp. AS3 and Sphingobacterium sp. AS8, demonstrated 3.06% and 2.01% (w/w) LDPE plastic weight loss over four weeks, respectively. Analysis by FTIR showed that both bacterial strains degraded the LDPE in the region of 3200–3400 cm −1 , which represents the OH group in a commercial LDPE polymer. Bacillus sp. AS3 caused the formation of a new range in the carbonyl group (C=O stretch) and the alcohol, carboxylic acid, esters, and ethers group (–C–O stretch). GC–MS analysis revealed various depolymerized compounds, such as alkane, alcohol, and carboxylic compounds, during LDPE degradation by Bacillus sp. AS3. Bacillus sp. AS3 illustrated esterase activity as 0.608 ± 0.004 U/mL after incubation. The proposed schematic of the LDPE biodegrading pathway by Bacillus sp. AS3 relies on the identification of depolymerized molecules as evidence. This suggests that Bacillus sp. AS3 possesses extracellular enzymes that break down LDPE into smaller molecules through depolymerization. Moreover, the surface of LDPE degraded by Bacillus sp. AS3 and Spingobacterium sp. AS8 was marked by cavities and a rough texture when observed under SEM analysis. This study provides microbial applications to reduce plastic pollution by utilising microorganisms to assimilate plastic waste as a carbon source.